Pathways for scaling up CSA practices in Senegal: Findings from stakeholder consultation - Worou, Nadine; Diouf, Bintou; Yessoufou, Nourou-Dine; Jaquet, Stéphanie; Huyer, Sophia; Gondwe, Therese; Chan, Derek; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project is a three-year initiative funded by the World Bank and implemented in six (6) African countries: Ethiopia, Ghana, Kenya, Mali, Senegal and Zambia. In Senegal, the project’s objective is to reach and impact over 300 000 farmers and value chain players with climate informed agro-advisories and new/improved climate smart-agriculture (CSA) packages and technologies by the end of 2023. Intervention pathways include outcomes on three levels: (1) enabling crop and livestock farming households to access Climate Information Services (CIS) and/or CSA technologies and practices; (2) reinforce the ability of value chain actors and influencers to offer climate-smart goods and services; (3) improving institutional performance to further benefit farming and (agro-) pastoralist households (Whitbread et al, 2023).